Metabolic Signatures in Lean MASLD: Current Insights and Future Directions - Babu, Ambrin Farizah (MDPI AG, 2026)
Lean metabolic dysfunction-associated steatotic liver disease (lean MASLD) challenges longstanding views that link hepatic steatosis primarily to obesity. Emerging as a distinct and under-recognized clinical entity, lean MASLD affects individuals with a normal body mass index (BMI), yet carries risks of cardiovascular disease, hepatocellular carcinoma, and liver-related mortality comparable to obesity-associated MASLD. The absence of overt metabolic dysfunction complicates diagnosis, revealing critical limitations in current screening frameworks centered on BMI. This review synthesizes evolving clinical insights and epidemiological trends in lean MASLD, and delineates its unique pathophysiological mechanisms. Recent advances in metabolomics have uncovered disease-specific disruptions in lipid and amino acid metabolism, bile acid signaling, and gut microbiota-derived metabolites. By integrating evidence from metabolic, genetic, and epigenetic domains, we identified promising biomarkers, and therapeutic targets that may support earlier detection and precision-guided treatment strategies.